Rancang Bangun Sistem Rekening Bersama untuk Keamanan Transaksi Online dengan Metode Brute Force String Matching - Sativa Wahyu Priyanto; Fatkhul Amin (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The development of the internet that is increasingly advanced makes activities that were previously carried out offline can be done online. One of them is trading. Trading conducted online can cover a wide and even unlimited scope. However, making online transactions without security is prone to fraud. Joint Account is the concept of a secure online transaction with a 3rd party as the middleman of the transaction. Searching for words that contain elements of fraud can minimize the occurrence of fraud. The Brute Force String Matching method is a straight and simple word search algorithm. Implementation of the joint account system can automatically search for words that contain elements of fraud. The word search results are displayed to the user in the form of a notification and a partial word sensor.